2017
DOI: 10.1002/cncr.30860
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in location of death of adolescents and young adults with cancer: A longitudinal, population study in California

Abstract: Overall, the majority of AYA cancer deaths occurred in a hospital, with a 5-year shift to more in-home deaths that abated after 1995. In-hospital deaths were more common among younger patients, patients of minority race/ethnicities, and those with a leukemia or lymphoma diagnosis. Further study is needed to determine whether these rates and disparities are consistent with patient preferences. Cancer 2017;123:4178-4184. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…In contrast, Hispanic ethnicity significantly increased the odds of PICU death within this large PPO patient population. Ethnic disparities involving location of death for children with cancer have been suggested by two prior studies, in which Hispanic patients were more likely to die in the hospital setting compared with non-Hispanic patients [26,27]. Our findings suggest that these disparities may extend across the PPO population as well.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In contrast, Hispanic ethnicity significantly increased the odds of PICU death within this large PPO patient population. Ethnic disparities involving location of death for children with cancer have been suggested by two prior studies, in which Hispanic patients were more likely to die in the hospital setting compared with non-Hispanic patients [26,27]. Our findings suggest that these disparities may extend across the PPO population as well.…”
Section: Discussionsupporting
confidence: 65%
“…A previous study conducted at this institution 8 years ago likewise showed that race did not affect EOL care planning or resuscitation status for children with cancer, but that study did not query potential disparities related to location of death [25]. To our knowledge, only two other studies have investigated the effect of race on location of death specifically in pediatric patients with cancer, in which black children, adolescents, and young adults were more likely to die in the hospital [26,27]. The lack of racial disparities identified in the two studies out of this institution may speak to broad financial interventions that level the socioeconomic playing field for all comers at this cancer center; however, further research is needed to explore this hypothesis and better describe racial disparities around EOL care for PPO patients and their families.…”
Section: Discussionmentioning
confidence: 93%
“…48 in care for Asian American patients. 52 For example, one study using Medicare claims demonstrated that the hospital death rate for patients with cancer was 22% in 2010 53 ; the current study, which included all patients who died of cancer in the United States in 2010, indicated that this rate was higher at 28%. Although all racial groups demonstrated a temporal decrease for hospital death rates within the last 17 02 03 04 05 06 07 08 09 10 11 12 13 14 15 99 00 01 02 03 04 05 06 07 08 09 10 11 12 13 14 15 99 00 01 02 03 04 05 06 07 08 09 10 11 12 13 14 15 99 00 01 02 03 04 05 06 07 08 09 10 11 12 13 14 years, the results of the current study highlight that large disparities remain.…”
Section: Discussionmentioning
confidence: 60%
“…In this context, EOL trajectories represent utilization patterns prior to the EOL in regards to costs, provider visits, hospitalizations, interventions, and general access to the health care system 1. Of the reports that exist, most focus on AYA with cancer 15. Roughly three-fourths of young people who die do so in an intensive care setting with numerous burdensome symptoms and distress at the EOL 6.…”
Section: Introductionmentioning
confidence: 99%
“…Even within the adolescent and young adult age group, preliminary evidence suggests that young adults (aged 20–24 years) are at great risk due to care transitions both in providers and insurance coverage, but most of this literature has been limited to those with cancer diagnoses 5,10,11. To our knowledge, examination of hospice care use has not yet been explored for young people who are covered through private insurance.…”
Section: Introductionmentioning
confidence: 99%